2018
DOI: 10.1111/jam.14052
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of glutathione on promoting 2-keto-l-gulonic acid production in vitamin C fermentation system

Abstract: Glutathione is proved to be effective to relieve oxidative stress. The promotion effects of GSSG and GSH on 2-KGA production could help to further explore the optimization of co-culture fermentation process for Vc industrial production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The addition of siderophores also upregulated the expression of genes sod at 32 and 52 h and katA at 12 h and 32 h in K. vulgare . Superoxide dismutase (SOD) scavenges ROS, and catalase (CAT) decomposes hydrogen peroxide (H 2 O 2 ) [31]. NADPH quinone reductase (MdaB) has been reported to maintain cellular resistance against oxidative stress and gene expression of MdaB was upregulated to remove lipid peroxidation [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of siderophores also upregulated the expression of genes sod at 32 and 52 h and katA at 12 h and 32 h in K. vulgare . Superoxide dismutase (SOD) scavenges ROS, and catalase (CAT) decomposes hydrogen peroxide (H 2 O 2 ) [31]. NADPH quinone reductase (MdaB) has been reported to maintain cellular resistance against oxidative stress and gene expression of MdaB was upregulated to remove lipid peroxidation [40].…”
Section: Discussionmentioning
confidence: 99%
“…In the 2-KLG fermentation process, the addition of various nutritional factors (e.g., glutathione, [31] gelatin [32], and rare earth elements [33]) affect the fermentation efficiency. Although some biomolecules (i.e., amino acids, antioxidant enzymes, vitamin B) have been reported to promote the growth and 2-KLG production of K. vulgare based on omics research, there are some metabolites that have not been mentioned [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Ma et al observed that addition of glutathione (GSH) promotes the transport of thiamin (vitamin B 1 )/thiamin pyrophosphate (TPP), 46,47 enhances the tricarboxylic acid (TCA) cycle and PPP pathway, and enhances cell resistance of K. vulgare to reactive oxygen species (ROS), rendering the strain better for growth and 2-KGA production under reducing environmental conditions. 48 In addition, a comparison of the growth of K. vulgare Hbe602 on various carbon sources (L-sorbose, D-mannitol, Dsorbitol, D-fructose, and D-glucose) revealed the possible presence of related metabolic pathways for D-sorbitol utilization, 40 with the observed growth showing the following trend: D-sorbitol > D-mannitol > L-sorbose > D-glucose > Dfructose. A minor quantity of 2-KGA was obtained when Dsorbitol was employed as a carbon source, suggesting that the metabolic pathway for conversion of D-sorbitol to 2-KGA exists in K. vulgare Hbe602.…”
Section: Characteristics Of Key Strains Employed In the Classic Two-s...mentioning
confidence: 99%
“…Ma et al observed that addition of glutathione (GSH) promotes the transport of thiamin (vitamin B 1 )/thiamin pyrophosphate (TPP), , enhances the tricarboxylic acid (TCA) cycle and PPP pathway, and enhances cell resistance of K. vulgare to reactive oxygen species (ROS), rendering the strain better for growth and 2-KGA production under reducing environmental conditions …”
Section: Characteristics Of Key Strains Employed In the Classic Two-s...mentioning
confidence: 99%